Strategic Management for IT Services on Outsourcing Security Company - Lydia Wijaya; Indra Kharisma Raharjana; Endah Purwanti (Journal of Information Systems Engineering and Business Intelligence, 2018)
Information Technology (IT) is used by many organizations to enhance competitive advantage, but many outsource security firms have not used IT in their business processes. In this research, we will design Strategic Management for IT Services for outsourcing security company. We use an outsourcing security company as a case study of IT Strategy Management for IT Services development. The purpose of this study is to create an IT services strategy for security outsourcing companies. The framework used is the ITIL (Information Technology Infrastructure Library) framework service strategy in strategy management for IT services process. There are several steps taken in the making of the strategy: (a) Strategic assessment stage to analyzed internal and external factors of the company. (b) Strategy generation by creating the strategic plan. (c) Strategy execution to determine the tactical plan. And (d) strategy measurement and evaluation. This study produced the proposed IT service system that suits the needs of the company in the form of strategic, tactical plans and strategy measurement. This result can be used as the foundations of IT service development in outsourcing security company. In the process of this study, we work closely with stakeholders; every work product has been verified and validated by stakeholders.